2017
DOI: 10.4336/2017.pfb.37.90.983
|View full text |Cite
|
Sign up to set email alerts
|

Alumínio estimula o crescimento radicular de erva-mate?

Abstract: A toxicidade por Al em plantas se dá de várias maneiras, sendo a inibição do crescimento radicular uma das primeiras a se expressar, embora não seja prontamente perceptível em razão do hábito de crescimento das raízes. O objetivo desse trabalho foi avaliar a tolerância da erva-mate ao Al por meio do crescimento de raízes de mudas submetidas a doses crescentes do elemento. Para isso, testaram-se, três clones (C1, C2 e C3), doses de 100, 500, 1.000 e 2.000 μmol L-1 de Al (AlCAlCl36H2O) e um controle sem Al. Após… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The adaptation of yerba mate to tolerate Al can be considered an important evolutionary characteristic because its natural area of distribution is in acidic soils with high Al 3+ saturation (REISSMANN et al, 1999), such as in this study where values higher than 75% was observed (Table 1). The Al 3+ in high concentration in soil solutions could provoke root toxicity; however, Benedetti et al (2017) reported that Al stimulates root growth in yerba mate.…”
Section: Elemental Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation of yerba mate to tolerate Al can be considered an important evolutionary characteristic because its natural area of distribution is in acidic soils with high Al 3+ saturation (REISSMANN et al, 1999), such as in this study where values higher than 75% was observed (Table 1). The Al 3+ in high concentration in soil solutions could provoke root toxicity; however, Benedetti et al (2017) reported that Al stimulates root growth in yerba mate.…”
Section: Elemental Compositionmentioning
confidence: 99%
“…A number of factors control the elemental composition of yerba mate leaves, for instance, the genetics (BENEDETTI et al, 2017;BARBOSA et al, 2018), leaf age, time between harvesting, index of light (JACQUES et al, 2007), variation between leaves and fruits (BARBOSA et al, 2015), and soil attributes (REISSMANN et al, 1999;CARNEIRO, 2004;BARBOSA et al, 2018). Considering that yerba mate leaves are meant for human consumption, it is necessary to identify its elemental composition and its relationship with soil proprieties, because the soil chemistry can determine the elemental composition and consequently the raw material quality.…”
Section: Introductionmentioning
confidence: 99%
“…Data transformation have been used frequently to approximate the residuals to the normal distribution and to achieve homoscedasticity (Sokal & Rohlf, 2012). For example, in Brazilian Journal of Forestry Research, analysis of variance was one of the most applied statistical test, as can be evidenced in several papers (Amaral et al, 2013;Faria et al, 2013;Freitas et al, 2013;Guareschi & Pereira, 2013;Guimarães Junior et al, 2013;Haliski et al, 2013;Lucena et al, 2013;Maeda & Bognola, 2013;Oliveira & Alixandre, 2013;Pias et al, 2013;Rocha et al, 2013;Rosado et al, 2013;Rossa et al, 2013;Santos et al, 2013;Ataíde et al, 2014;Bastos et al, 2014;Carpanezzi & Gualtieri, 2014;Dias Júnior et al, 2014;Flores et al, 2014;Leite et al, 2014;Medeiros et al, 2014;Mossanek et al, 2014;Oliveira et al, 2014;Prevedello et al, 2014;Protásio et al, 2014;Silva et al, 2014;Souza et al, 2014;Téo et al, 2014;Turchetto & Fortes, 2014;Alves et al, 2017;Benedetti et al, 2017;Boscardin et al, 2017;Cerqueira et al, 2017;Dutra et al, 2017;Freire et al, 2017;Lima & Stap...…”
Section: Some Relevant Points About the Proposed Transformationsmentioning
confidence: 99%
“…Aluminum toxicity has not been a limiting factor for growth of yerba mate since most plantations do not receive lime to correct soil acidity (Marques et al, 2013). Furthermore, there are indications of greater growth of root systems when Al is used in nutrient solutions (Benedetti et al, 2017). However, the combination of abiotic factors (e.g., high acidity and high Mn concentrations in some soils) with genetic factors of this species, suggests that yerba mate is a species with a high capacity for accumulating metals.…”
Section: Introductionmentioning
confidence: 99%